Effect of Glycolyl Segment on Structure and Performances of Degradable Polyurethane Foam of Poly(ε‐Caprolactone‐r‐Glycolide) Copolymer - Qiuming, Jin; Zhengzhe, Zhou; Dongyang, Liu; Qi, Xia; Shinuo, Zhang; Wenjie, Yu; Zhongyong, Fan (Polymer engineering and science, 2025)
ABSTRACT A series of degradable flexible polyurethane foams were successfully prepared using a novel synthesized three‐armed poly(ε‐caprolactone‐r‐glycolide) (P(CL‐r‐GA)) as feedstocks. These foams with core density of about 60 kg/m3 and cell diameter in the range of 220–348 μm showed high indentation force deflection and low rebound resilience, thus exhibiting excellent loading capacity and impact resistance. By adjusting the feed ratio of GA monomer, the effect of glycolyl segment on the foam compression and resilience properties is investigated. It is found that the incorporation of GA evidently improved the melt viscosity of the triols and led to a decrease in average cell diameter. Meantime, enhanced hydrogen bonding interactions between polyester segment and urethane or urea segment caused by glycolyl segment were observed among polyurethane chains. Because of the enhanced intermolecular interactions, the foam was endowed with high impact absorption performance with low ball rebound value and long recovery time. The Rusch model and Gibson model were used to analyze the mechanism of its mechanical behavior, and the results demonstrated that physical crosslinking formed by the hydrogen bonding of polyurethane chains led to an increase in Young's modulus of the foam at small deformation. Meanwhile, improved indentation force deflection at large deformation was mainly attributed to cell size reduction. Enhanced hydrogen‐bonding interaction and reduced average cell size caused by glycolyl segment endowed the degradable polyurethane foam with high impact absorption performance.